2018
DOI: 10.21053/ceo.2017.01109
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Volatile Sulfur Compounds in Adult and Pediatric Chronic Tonsillitis Patients Receiving Tonsillectomy

Abstract: Objectives. To study the volatile sulfur compound (VSC) concentration profile in chronic tonsillitis patients before and after tonsillectomy, and to evaluate the difference between adult and pediatric (children and adolescents) patients.Methods. Thirty adult patients (older than 20 years old) and 30 pediatric patients (younger than 20 years old) who were assigned to get tonsillectomy due to chronic tonsillitis were enrolled in this prospective nonrandomized clinical study. The concentrations of the three main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…In the present study, a significant reduction in clinical halitosis (VSCs concentrations) was detected in more than half of the children following FMR under GA. Interestingly, similar findings were reported in the medical field, where halitosis in children has received considerable attention [ 29 , 33 ]. Choi et al and Dinc et al Used OralChroma TM to evaluate the VSCs concentrations in children and adolescents before and after tonsillectomy and adenoidectomy, respectively, under GA.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the present study, a significant reduction in clinical halitosis (VSCs concentrations) was detected in more than half of the children following FMR under GA. Interestingly, similar findings were reported in the medical field, where halitosis in children has received considerable attention [ 29 , 33 ]. Choi et al and Dinc et al Used OralChroma TM to evaluate the VSCs concentrations in children and adolescents before and after tonsillectomy and adenoidectomy, respectively, under GA.…”
Section: Discussionsupporting
confidence: 80%
“…Differences in the means between two dependent variables (matched pairs) were compared at α = 0.05 with a 0.4 effect size and power of 0.9 [ 29 ]. The sample size was calculated to be 50 children in order to detect significance.…”
Section: Methodsmentioning
confidence: 99%
“…To these volatile substances belong sulfur compounds, aromatic compounds, amines, short-chain fatty or organic acids, alcohols, aliphatic compounds, aldehydes, and ketones (Table 1) [25,[30][31][32][33]. It is considered that hydrogen sulfide, methyl mercaptan, and dimethyl sulfide are the main volatile compounds in IOH [34][35][36][37]. In many studies, the measurement of malodor substances concerns only volatile sulfur compounds (VSCs).…”
Section: Volatile Compoundsmentioning
confidence: 99%
“…Increasing evidence has suggested that certain oral bacteria and chronic inflammation (e.g., tonsillitis or periodontitis) are associated with high concentrations of hydrogen sulfide in the oral cavity [Salako and Philip, 2011;Takeshita et al, 2012;Ren et al, 2016;Choi et al, 2018]. Furthermore, Ag 2 S is a dense black solid that is insoluble in all solvents, and its solubility product constant is much lower than that of Ag 2 O, Ag 3 PO 4 , and other silver compounds [Harris, 2015;Rumble, 2018].…”
Section: Silver Penetration In Carious Lesionsmentioning
confidence: 99%